Analysis of the Effect of Clothing Color Spectrum on the Absorption and Reflection Coefficient of Solar Radiation - Kusumah, Abel Indra; Rahardiansyah, Bagus Dwi; Pika, Pika; Aulia, Caca; Qeianu Rafly, Marzhal (Ann Publisher, 2024)
Clothing plays an important role in maintaining body comfort, especially in extreme weather conditions, but people often prefer clothes based on trends rather than thermal effectiveness. This study aims to examine the influence of clothing color on the increase in fabric surface temperature in various environmental conditions. The research method was carried out through experiments using different colored fabrics indoors and outdoors, as well as descriptive surveys to understand people's preferences and habits. The results of the experiment showed that dark-colored clothes absorbed heat more than light-colored clothes, while the survey revealed that most respondents still chose dark clothes for aesthetic reasons. This study contributes to a scientific understanding of the effect of clothing color on thermal comfort and underscores the need for public education to balance comfort with clothing style. This research is expected to be a guide in choosing clothes that suit thermal and aesthetic needs.